A study on the mechanical and corrosion behaviour of bronze – TiB2 metal matrix composites. (2021) - Venkatesan, Su.; Jerald, J.; Asokan, P.; Harichandran, R.
Abstract: In the current scenario, there is a surge in the infusion of composite materials for a wider range of applications. Metal Matrix Composites offered numerous benefits regarding the enhancement of mechanical behaviour and also the corrosion behaviour under the influence of reinforcements. In this research, the bronze material, selected as the base material and TiB2, added as the reinforcement in different weight (wt) percentages (2%, 4%, and 6%). The liquid pathway (stir casting) is administered for composite preparation. This work focusses on the hardness, tensile strength and compressive strength of the prepared samples and also their corrosion behaviour. The presence of the reinforcements confirmed through XRD analysis and EDAX obtained with FESEM. Fractography studies are also conducted through FE-SEM. The results disclosed that the addition of reinforcement improves the mechanical characteristics of the composite samples. Corrosion properties indicated slight marginal improvement.